2005
DOI: 10.1111/j.1600-0420.2005.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in glaucoma patients' knowledge, need for information and expectations of treatments

Abstract: ABSTRACT.Purpose: To study the specific items for which socioeconomic differences in glaucoma patients' knowledge, need for information and expectations of treatments exist, with the aim of developing a patient education programme. Methods: A total of 44 randomly selected ophthalmologists assigned 166 consecutive outpatient glaucoma patients to complete a questionnaire that had been systematically developed based on focus group interviews, suggestions from several experts and a pilot test. Topics included know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 29 publications
6
51
1
2
Order By: Relevance
“…Patients' ability to manage glaucoma medications can differ according to their socioeconomic status, health-care experiences, and health beliefs. [10][11][12] Understanding individual patients' needs and providing follow-up support accordingly may prove to be more effective in promoting adherence than a standardised approach.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' ability to manage glaucoma medications can differ according to their socioeconomic status, health-care experiences, and health beliefs. [10][11][12] Understanding individual patients' needs and providing follow-up support accordingly may prove to be more effective in promoting adherence than a standardised approach.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of a study conducted in the Netherlands emphasised that disadvantaged patients with glaucoma should be educated especially with regard to the risk factors and consequences of the disease; the authors concluded that general knowledge about glaucoma and its treatment is directly related to positive treatment results. In the same study, patients of lower socioeconomic status needed more information about glaucoma, a factor which is often underestimated (6) . Ophthalmic campaigns are mainly intended to benefit a large number of poor people and should focus on factors such as target population, location of health care services, previous screening, and possible referral of patients to specialised services, among others (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The median educational support score for newly prescribed patients was 12 (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A sample of the information given is presented in Table 3.…”
Section: Observation Datamentioning
confidence: 99%
“…A lack of glaucoma knowledge is frequently cited as a major cause of poor adherence to ocular hypotensive therapy. [2][3][4][5][6][7] Inconsistencies have been found in the assessment of knowledge; questionnaires range from a small number of general questions to detailed questions about diagnostic procedures, 8 which can cause difficulties in identifying specifics gaps in knowledge that potentially affect adherence.…”
Section: Introductionmentioning
confidence: 99%